Studi Literatur : Pengungkapan Kecurangan Melalui Investigasi Audit Pada Badan Pemeriksa Keuangan - Debby Yusriliana; Linda Novia Sari; Avilla Anggun A; Tri Ratnawati (Jurnal Riset Akuntansi, 2023)
This study aims to analyze the effect of applying forensic accounting, investigative auditing, and auditor professionalism on fraud disclosure. This research is a Literature Review, in which we will provide an opinion on the results of previous research. The test results indicate that investigative audits and state financial loss calculation audits have a significant positive effect on corruption crimes. The results of this study are expected to enrich the literature for the development of science and also as material for consideration for the Audit Board of the Republic of Indonesia in disclosing acts of corruption.